Option value for a contract in trade for weaned piglets in Finland - Pietola, Kyösti S.; Wang, H. Holly (Maatalouden taloudellinen tutkimuslaitos, 1999)
This paper estimates farmer s choice between standard and organic farming technologies in Finland over the period of 1994-97. The choice between standard and organic technologies is modeled as a discrete choice, which results from a finite period dynamic optimization problem. The optimization problem is numerically solved by iterating on Bellman equation backwards in time while the unknown parameters of the model are estimated by a switching type Probit MLE. The maximized values of the uncertain revenue streams are simulated by Monte Carlo simulation technique. The results suggest that they have been the decreasing prices and returns to the standard farming as well as the excess subsidies granted for organic farming that have been triggering switches to the organic technology. This implies that even income neutral policy reforms, which decrease price support and compensate the resulting income losses by direct income transfers, will increase farmer incentives to switch to the organic farming technology. The switch has also been encouraged in farms having large land areas and low yields. The switch has, on the other hand, been discouraged by livestock intensive or otherwise either labor or capital intensive production. In other words, farmers who have had the best opportunities to sustain their income by extensive, low input farming has been the most eager to switch and collect the excess subsidies granted to the organic farming technology.
Keywords: Ma; vertikaalinen koordinaatio; reaalioptiot; investoinnit; sopimukset; sikatalous; vertical coordinaation; investments; real options; hog industry